2017
DOI: 10.15252/emmm.201607305
|View full text |Cite
|
Sign up to set email alerts
|

Seeding and transgenic overexpression of alpha‐synuclein triggers dendritic spine pathology in the neocortex

Abstract: Although misfolded and aggregated α‐synuclein (α‐syn) is recognized in the disease progression of synucleinopathies, its role in the impairment of cortical circuitries and synaptic plasticity remains incompletely understood. We investigated how α‐synuclein accumulation affects synaptic plasticity in the mouse somatosensory cortex using two distinct approaches. Long‐term in vivo imaging of apical dendrites was performed in mice overexpressing wild‐type human α‐synuclein. Additionally, intracranial injection of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
69
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 89 publications
16
69
1
Order By: Relevance
“…Blumenstock et al. () reported that α‐synuclein accumulation induced by intrastriatal injection of PFFs caused dendritic spine loss in the mouse somatosensory cortex.…”
Section: Alpha‐synuclein Overexpression Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Blumenstock et al. () reported that α‐synuclein accumulation induced by intrastriatal injection of PFFs caused dendritic spine loss in the mouse somatosensory cortex.…”
Section: Alpha‐synuclein Overexpression Modelsmentioning
confidence: 99%
“…For example, Nouraei et al (2018) injected PFFs into mice hippocampus and caused formation of α-synuclein-positive inclusions, which were insufficient to cause hippocampal cell death, but their expansion was negatively correlated with memory capacity. Blumenstock et al (2017) reported that α-synuclein accumulation induced by intrastriatal injection of PFFs caused dendritic spine loss in the mouse somatosensory cortex.…”
Section: Preformed Alpha-synuclein Fibrils Modelmentioning
confidence: 99%
“…These presynaptic aggregates correspond to reduced dendritic spine density, suggesting that they impact synaptic function. Dendritic spine density is also reduced in rodent models of α‐syn aggregation . Indeed, fibril‐induced formation of α‐syn aggregates causes major reduction in mushroom spine density at a time point preceding neuronal death .…”
Section: Genes Implicated In Pd That Play a Role At The Presynaptic Tmentioning
confidence: 99%
“…Dendritic spine density is also reduced in rodent models of α-syn aggregation. 154 Indeed, fibril-induced formation of α-syn aggregates causes major reduction in mushroom spine density at a time point preceding neuronal death. 11 Exposure of neurons from α-syn knockout mice to fibrils does not affect spine density, demonstrating that corruption of endogenous α-syn causes synaptic structural defects.…”
Section: α-Syn and Presynaptic Dysfunctionmentioning
confidence: 99%
“…Moreover, dendritic spine loss and compromised neuronal and network activities have been observed before neuronal death after exposure to extracellular α-syn (e.g. PFFs) or in α-syn transgenic mice (e.g., A53T and WT-α-syn overexpression) [10,12,49,50,[58][59][60]. However, the mechanism through which α-syn abnormalities affect synaptic transmission remains unclear.…”
Section: Discussionmentioning
confidence: 99%